MULTICULTURAL EDUCATION MANAGEMENT THEORY - Khairun Nizar, M. Alang (UIN Sumatera Utara Medan, 2025)
Education is the primary foundation for developing good individuals and societies. In an era of increasing globalization and interconnectivity, education faces the challenge of managing the diversity of cultures, religions, and social backgrounds of students. The method for writing the research results of this review article begins with a gap analysis followed by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The PRISMA method consists of five stages: 1) defining eligibility criteria, 2) determining information sources, 3) selecting data, 4) collecting data, and 5) collecting data. This curriculum emphasizes four main aspects. The results of the study indicate that a series of management processes are necessary to implement multicultural values education efforts to shape religious character in students in the school environment. These efforts are realized through education, because it is through education that a person's basic character, intellectual, and emotional abilities can be formed in viewing the surrounding reality. This can be interpreted as meaning that education is the process of transmitting culture and simultaneously learning societal norms, through specific methods, so that people acquire knowledge, understanding, and behaviors appropriate to their needs.